1989
DOI: 10.1007/bf00008155
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the community structure of planktonic ciliated protozoa relative to trophic state in Florida lakes

Abstract: The planktonic ciliate populations of 30 Florida lakes constituting a broad trophic gradient were examined to determine the response of protozoan community structure to increasing eutrophication. Both ciliate abundance and biomass were strongly related to lake trophic state. Comparison of the Florida data base with a comparable north temperate lake group indicated that subtropical lakes generally possess higher ciliate abundance and biomass at a given trophic state than temperate lakes. However the equations d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 15 publications
2
40
1
Order By: Relevance
“…During half of the study years, ciliate biomass in July surpassed that of daphnids, showing that ciliates exerted a major grazing pressure on phytoplankton, not only in spring but increasingly also in summer, given the higher weight-specific grazing rates of the smaller-sized ciliates. In contrast, crosslake comparisons in Florida, Germany and Finland found that decreasing trophic status resulted in proportionally lower ciliate biomass (Bays & Crisman 1983, Beaver & Crisman 1989, Mathes & Arndt 1994 for the spring peak, Zingel et al 2002). However, the relative contribution of ciliates to total zooplankton biomass did not vary with trophic status in a study of Quebec lakes (Pace 1986).…”
Section: Discussionmentioning
confidence: 94%
“…During half of the study years, ciliate biomass in July surpassed that of daphnids, showing that ciliates exerted a major grazing pressure on phytoplankton, not only in spring but increasingly also in summer, given the higher weight-specific grazing rates of the smaller-sized ciliates. In contrast, crosslake comparisons in Florida, Germany and Finland found that decreasing trophic status resulted in proportionally lower ciliate biomass (Bays & Crisman 1983, Beaver & Crisman 1989, Mathes & Arndt 1994 for the spring peak, Zingel et al 2002). However, the relative contribution of ciliates to total zooplankton biomass did not vary with trophic status in a study of Quebec lakes (Pace 1986).…”
Section: Discussionmentioning
confidence: 94%
“…The influence of the trophic state on the protozooplankton has been pointed out for other environments (Beaver & Crisman, 1989;Hwang & Heath, 1997). At the species level, several organisms are considered good indicators of the distinct conditions found between sampling sites.…”
Section: Discussionmentioning
confidence: 99%
“…are very common. They can be found at any time of the year, and in oligotrophic as well as in eutrophic lakes (Pace 1982, Beaver & Crisman 1989, Foissner et al 1991, Miiller et al 1991. Small oligotrichous ciliates eat bacteria and autotrophic picoplankton, while ingestion of larger food particles appears to be rare (Simek et al 1996).…”
Section: Discussionmentioning
confidence: 99%